"Standing by Our Principles": The Trades and Labor Congress of Canada and Immigration, 1933-1939 - Goutor, David (Just Labour: A Canadian Journal of Work and Society, 2007)
This paper explores the approach of Canada's largest labour central, the Trades and Labor Congress (TLC), to immigration from 1933 to 1939. This was a unique period in Canada's immigration history, as in 1930 the government responded to the onset of the Great Depression by closing the gates to almost all immigration for the first time since Confederation, and by 1933 there was no doubt that the gates would remain closed for some time. Despite this dramatic change, Canadian labour leaders stood by their longstanding views on immigration through to the end of the 1930s. Although the level of concern about immigration predictably declined, TLC leaders generally gained confidence that their established views had widespread support. This confidence encouraged unionists to pose as protectors of immigrants against hardship in Canada. It also assured them that they did not have to devote as much energy as in earlier periods to agitating for the deportation of some immigrants, or to their longtime favourite cause, restricting immigration from Asia and southern and eastern Europe. Altogether, changes in the economy and immigration rates did not necessarily entail changes in labour's attitudes. A number of other factors, including ideological trends within the movement, prevailing attitudes towards race and gender, and the efforts of groups advocating immigration served to entrench labour's views even more deeply in the 1930s.